PENGARUH PEMBERDAYAAN DAN SELF EFFICACY TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDY PADA INSPEKTORAT PROVINSI JAWA TENGAH) - 11.42.02.0117, Siti Nur’Aini (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research in conduct to test and analyze (1) The influence of empowerment and self efficacy toward commitment organizational, (2) The influence of empowerment, self efficacy and commitment organizational toward employee performance. Located research in Inspektorat Provinsi Jawa Tengah, Research sample amount to 90 respondent by using census. This research is explanatory research. Measurement to use scale likert with 7 (seven) alternative answer. This result of multiple regression analyze show coefficient determination amount 0.333 or with other word different on commitment organizational which have to description by The influence of empowerment and self efficacy amount 33.3 percent. Different on performance which have to description by empowerment, self efficacy and commitment organizational amount 54,1 percent. This research shows these following result (1) by empowerment and self efficacy have on significant effect toward commitment organizational, (2) by empowerment, self efficacy and commitment organizational have an significant effect to employee performance. Keyword: empowerment, self efficacy , commitment and employee performance